A COMPARATIVE ANALYSIS OF TCP/IP AND OSI NETWORK MODELS IN MODERN COMPUTER SYSTEMS - Khanna, Kanika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This document covers both the OSI and TCP/IP models in detail since they are essential building blocks in science and network engineering. The analysis looks at how each model developed, how their designs were formed, what their different operation levels involve and the practical applications they each support for communication and data transfer. Although the OSI framework is studied as a basic reference and knowledge builder organised by seven layers, the TCP/IP framework is considered more practical and relevant, holding a key place in modern online networking due to four main layers. The document covers how data encapsulation achieves sending, organizing, steering and handling errors. It points out that layered abstraction is essential for fixing network problems more quickly and helping different devices work together. OSI model theory provides solid foundations, detailed analysis shows, whereas TCP/IP model delivers flexibility and is highly effective with networks that are both distributed and can handle a lot of data. Moreover, common network protocols such as HTTP, FTP, DNS, IP and TCP are examined to expose how protocol stacks are used in everyday network situations. The research details how systems handle various tasks associated with network communication and shows how these roles adjust to the growing needs of modern online services.